Phenomenology of autobiographical memory in blind and sighted individuals - Yılmaz, Engin. (Thesis (M.A.)-Bogazici University. Graduate Institute of Social Sciences, 2005., 2005)
This study compared the phenomenology of autobiographical and flashbulb memories in sighted and congenitally totally blind individuals. Participants recalled autobiographical memories in response to six cue words, and recalled how they heard about the September 11, 2001 attacks on the Twin Towers in New York City. They filled out the Autobiographical Memory Questionnaire (AMQ) for all these memories. Results showed that blind participants gave higher ratings to the belief variables. In addition, as expected, while blind participants were higher than sighted participants on auditory imagery, sighted participants gave higher ratings to the visual imagery variable than blind participants. The prediction of recollection and belief factors by component processes with multiple regression analysis indicated that story have become very significant contributer of recollection and belief factors for sighted individuals and emotion was significant predictor of those for blind individuals. For both group the significance of hear and language related factors were also seen as in the study of Gülgöz & Rubin (2001). The lack of vision could be compansated especially with the contribution of auditory imagery, setting and language related factors on blind participants. The results were discussed on the basis of Rubin's (2003, 2005) theoretical formulation of autobiographical memory.
Keywords: Autobiographical memory.; Flashbulb memory.; Blind.